Analysis of macular retinal thickness in polyarteritis nodosa using spectral domain optical coherence tomography - Che-Ning Yang; Chia-Ping Chen; Yi-Ting Hsieh (Journal of Ophthalmic Inflammation and Infection)
Abstract Purpose To identify the macular retinal layer thickness changes in polyarteritis nodosa (PAN) patients without pathological findings appearing in color fundus photography (CFP), and to investigate the correlations with disease durations. Methods A total of 24 PAN patients who had been for 3 years or more and underwent SD-OCT were recruited from the UK Biobank, with exclusions for diabetes, eye disease, or abnormal CFP findings. Only the right eyes were included, with each PAN patient paired one-to-one with a control matched for age, sex, and ethnicity. Paired t-tests or Wilcoxon Signed-Rank tests were used to assess the differences in thickness of different retinal layers between groups, followed by linear regression analysis to evaluate the correlations with disease durations. Results PAN patients had significantly thinner retinal nerve fiber layer (RNFL) by 12.27% (mean ± standard deviation = 27.39 ± 8.94 μm for PAN patients and 31.22 ± 5.57 μm for controls, p = 0.048) and thinner outer plexiform and outer nuclear layers (OPL-ONL complex) by 10.67% (44.93 ± 6.59 μm for PAN patients and 50.31 ± 7.60 μm for controls, p = 0.032). Visual acuity and the whole macular thickness showed no statistical difference. The RNFL was thinned by 1.22 μm per year of disease progression (95% confidence interval: 0.12, 2.32, p = 0.042). Conclusions PAN patients without visual impairments or abnormal CFP findings may exhibit significant thinning in RNFL and OPL-ONL complex. SD-OCT may serve as a useful tool for early screening of ophthalmic changes in PAN.